2021
DOI: 10.1158/1078-0432.ccr-20-2571
|View full text |Cite
|
Sign up to set email alerts
|

Camrelizumab in Combination with Apatinib in Patients with Advanced Hepatocellular Carcinoma (RESCUE): A Nonrandomized, Open-label, Phase II Trial

Abstract: Purpose: We assessed the efficacy and safety of camrelizumab [an anti-programmed death (PD-1) mAb] plus apatinib (a VEGFR-2 tyrosine kinase inhibitor) in patients with advanced hepatocellular carcinoma (HCC). Patients and Methods: This nonrandomized, open-label, multicenter, phase II study enrolled patients with advanced HCC who were treatment-naïve or refractory/intolerant to first-line targeted therapy. Patients received in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
388
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 434 publications
(414 citation statements)
references
References 19 publications
17
388
9
Order By: Relevance
“…However, it was unclear whether radiotherapy can be safely administered to patients also receiving the PD-1/PD-L1 inhibitors and targeted therapy combination. It should be noted that the safety profile of triple therapy in this population was similar to those reported in previous studies of two-drug combination therapy (8)(9)(10). In our study, the most common TRAEs were rash, diarrhea, aspartate aminotransferase increase, alanine transaminase increase, decreased appetite, and fatigue.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, it was unclear whether radiotherapy can be safely administered to patients also receiving the PD-1/PD-L1 inhibitors and targeted therapy combination. It should be noted that the safety profile of triple therapy in this population was similar to those reported in previous studies of two-drug combination therapy (8)(9)(10). In our study, the most common TRAEs were rash, diarrhea, aspartate aminotransferase increase, alanine transaminase increase, decreased appetite, and fatigue.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, atezolizumab plus bevacizumab became the new standard of first-line therapy. Furthermore, lenvatinib plus pembrolizumab and camrelizumab in combination with apatinib in HCC have also received encouraging results from a Phase 1b and 2 study, respectively ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, considering the potential synergistic efficacy of targeted therapy combined with immune checkpoint inhibitor, apatinib plus camrelizumab might be a potentially effective combination for various tumors (15). For patients with advanced HCC, apatinib combined with camrelizumab achieved a 34.3% objective response as the first-line and 22.5% as the secondline therapy (16). Similar results were also observed in osteosarcoma, gastric cancer, advanced triple-negative breast cancer and a variety of other tumors (17)(18)(19).…”
Section: Introductionmentioning
confidence: 53%
“…Although camrelizumab combined with apatinib has achieved promising results in the treatment of various tumors, including hepatocellular carcinoma, osteosarcoma and triplenegative breast cancer, this regimen has not been reported in cholangiocarcinoma (16,17,19). Currently, most trials combining multitarget TKIs with PD-1 blockade for BTC are in the recruitment phase, and few studies have reported detailed results.…”
Section: Discussionmentioning
confidence: 99%
“…Median PFS was 5.7 and 5.5 months, and 12-month survival rates were 74.7% and 68.2%, respectively. Grade ≥3 TRAEs occurred in 77.4% of patients [49]. Finally, the VEGF Liver 100 trial evaluated the anti-PD-L1 avelumab in combination with axitinib (VEGF receptor 1/2/3 inhibitor) in treatment-naïve advanced HCC patients [50].…”
Section: Icis and Tkis/anti-vegfsmentioning
confidence: 99%